Genetic analysis of poplar (Populus deltoides Bartr.) clones for early generation selection - Singh, N.B.; Singh, Bikram; Kumar, Dinesh (The Indian Journal of Genetics and Plant Breeding, 2016)
The study aimed to select the best clones from a field trial of 69 newly developed clones and two check clones of Populus deltoides after 3 years of field performances. Growth traits were assessed for three growing seasons. Significant differences were detected among clones for plant height, stem diameter, estimated trunk volume and sylleptic branch number. Plant height, stem diameter and trunk volume had low to moderate (0.21 to 0.41) broad sense heritability (h2) values. Sylleptic branch number showed high genetic advance (77.53%) despite moderate h2. In nursery trial, the h2 estimates were moderate to high h2 (0.61 to 0.69) for growth traits. It is possible to apply selection on the basis of principal component analysis (PCA) accounting for a large part of the total variance in the observed growth relying on trunk volume followed by stem diameter, plant height and sylleptic branch number. The promising clones viz. FRI-AM-53, -70, -51, -6 and -45 outperformed the control clone G-48. Stem diameter showed high (0.97) genetic correlation with trunk volume and proved to be a reliable criterion for selecting for trunk volume.The set of 25 most promising clones based on PCA1 ranking will be effective for selection of clones at the age of three years.